Long-term variability of the mean sea level pressure field over the Black Sea - Islek, Fulya; Yuksel, Yalcin; Sahin, Cihan (MICHIGAN STATE UNIV PRESS, 2020)
This paper aims to evaluate spatiotemporal variability of the mean sea level pressure trends over the Black Sea using the gridded 40-year (1979-2018) reanalysis mean sea level pressure data from two different datasets. These datasets are the European Centre for Medium-Range Weather Forecasts ERA-Interim with a spatial resolution of 0.25 degrees and temporal resolution of six hours, and the National Centers for Environmental Prediction/Climate Forecast System Reanalysis with a spatial resolution of 0.5 degrees and temporal resolution of one hour. Data from both databases show that the mean sea level pressure tends to decrease towards the recent years over the entire Black Sea. The long-term averages of mean sea level pressure reflect the spatial variability over the Black Sea with much lower pressures in the eastern part of the Black Sea than that on the western side. The long-term variation is more intense in the eastern part of the Black Sea. Sea Level Anomaly over the Black Sea, spanning 26 years between 1993 and 2018, was analyzed using satellite altimetry data. It was found that there is a high Sea Level Anomaly where the mean sea level pressure is low, described by an inverted barometer response. The 39-year long Sea Surface Temperature Anomaly data (1981-2018) indicate the rising tendency in sea surface temperature towards recent years in the entire Black Sea. An inverse relationship is found between North Atlantic Oscillation index and sea surface temperature anomaly. On a seasonal scale, mean sea level pressure in winter (high-pressure system) is larger than that in summer (low-pressure system). Our analyses show that mean sea level pressure tends to decrease, sea surface temperature anomaly and sea surface temperature anomaly tends to increase in recent years over the Black Sea.
Keywords: atmospheric circulation; spatiotemporal variation; sea surface temperature; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources